Pemanfaatan Teknologi Drone untuk Pembelajaran Geografi Spasial di Tingkat Pendidikan Menengah Atas - Danardono Danardono; Priyono Priyono; Kartika Cindi Wulandari; Danis Novianto (Universitas Muhammadiyah Surakarta, 2022)
The emergence of a new era of society 5.0 requires every scientific field has high technology development, up-to-date, easily accessible, and internet-based, including geography major. One of the technologies that has developed in the geography major is the use of drone technology for mapping. However, technological developments in the field of geography have not been integrated into geography learning, especially at the secondary education level. This is due to the lack of scientific updates for educators at the secondary education level regarding the development of this technology. This is the background for the implementation of this service activity which aims to introduce and improve the understanding of teachers at the secondary education level in the use of drones for various geographical studies. The service is carried out in the form of socialization related to drone technology, training and drone operation simulations. The activity participants were very enthusiastic in participating in the activities and appreciated the implementation of interesting activities and provided a lot of knowledge for participants. In fact, participants asked for further activities that were more specific to discuss the use of drones in a particular study, from data collection to data processing.